Anisotropic swelling of thin gel sheets. Issue 8 (28th February 2015) - Nardinocchi, Paola; Pezzulla, Matteo; Teresi, Luciano
<x xml:space="preserve">Abstract</x> Extended Flory–Rehner free energy for anisotropic swelling of hydrogels, with applications to bilayered microstructured sheets, is described.